Superset versus traditional resistance training prescriptions: a systematic review and meta-analysis exploring acute and chronic effects on mechanical, metabolic, and perceptual variables - Zhang, X.; Weakley, J.; Li, H.; Li, Z.; García-Ramos, A. (Sports Medicine, 2025)
Background: Supersets are a time-efficient resistance training (RT) method that involve the sequencing of two exercises with little or no rest between them. However, despite their common implementation during RT, a comprehensive and quantitative review is still lacking. Objectives: The primary aim of this systematic review and meta-analysis was to compare the acute and chronic effects of superset and traditional set prescriptions on mechanical, metabolic, and perceptual variables. We also aimed to conduct subgroup analyses to determine the effect of different types of supersets (agonist-antagonist, similar biomechanical, and alternate peripheral supersets). Methods: A systematic literature search was conducted in PubMed, Web of Science, Embase, and EBSCO databases from inception to 10 February 2024. Studies written in English and meeting our inclusion criteria were included. Pooled meta-analysis and subgroup meta-analysis were performed using a random-effects model. Results: Nineteen studies involving 313 participants were included. Although there was considerable variance in certain outcomes, our estimated effects suggested that, compared with traditional set prescription, supersets allow for (1) a similar total number of repetitions [standardized mean differences (SMD) = - 0.03; p = 0.92] and volume load (SMD = 0.05; p = 0.86) with a shorter session duration and increased training efficiency (SMD = 1.74; p = 0.01); (2) higher blood lactate concentration during (SMD = 0.94; p = 0.03) and after (SMD = 1.13; p < 0.01) RT; (3) higher energy cost during RT (SMD = 1.93; p = 0.04); (4) similar creatine kinase concentration after RT (SMD = 0.22; p = 0.36), surface electromyography (SMD = 0.01; p = 0.98), acute muscle swelling (SMD = - 0.28; p = 0.36) and blood pressure (systolic blood pressure [SMD = 0.08; p = 0.71], diastolic blood pressure [SMD = - 0.05; p = 0.85], and mean arterial pressure [SMD = - 0.03; p = 0.88]); (5) higher rating of perceived exertion (SMD = 0.77; p = 0.02) and similar perceived recovery (SMD = 0.32; p = 0.33); and (6) similar chronic adaptations in maximal strength (SMD = 0.10; p = 0.36), strength endurance (SMD = 0.07; p = 0.81), and muscle hypertrophy (SMD = - 0.05; p = 0.87). The subgroup analysis revealed that utilizing agonist-antagonist supersets leads to a significant increase in the number of repetitions that are able to be completed compared with traditional sets (SMD = 0.68; p = 0.01). Similar biomechanical supersets led to less volume load (SMD = - 1.08; p < 0.01) compared with traditional sets. Conclusions: Supersets provide a time-efficient alternative to traditional RT, reducing session duration without compromising training volume, muscle activation, perceived recovery, or chronic adaptations in maximal strength, strength endurance, and muscle hypertrophy. Thus, supersets can be effectively implemented by athletes with busy schedules and RT enthusiasts whose main barrier to exercise is time. However, it should be noted that supersets generally induce higher internal loads, more severe muscle damage, and increased perceived exertion, potentially necessitating extended recovery times between sessions. Additionally, superset RT may have a similar potential to traditional RT in eliciting post-exercise hypotension. Regarding different types of supersets, agonist-antagonist supersets are more suitable for maintaining training volume, while similar biomechanical supersets concentrate stimulation on the same muscle group, compromising volume load.